Virus-like particles identify an HIV V1V2 Apex-1 binding neutralizing antibody that lacks a protruding loop - Cale, Evan M; Gorman, Jason; Radakovich, Nathan A; Crooks, Ema T; Osawa, Keiko; Tong, Tommy Yuh Koon * (Elsevier, 2017)
Most HIV-1-specific neutralizing antibodies isolated to date exhibit unusual characteristics that complicate their elicitation. Neutralizing antibodies that target the V1V2 apex of the HIV-1 envelope (Env) trimer feature unusually long protruding loops, enabl them to penetrate the HIV-1 glycan shield. As antibodies with loops of requisite length are created through uncommon recombination events, an alternative mode of apex binding has been sought. Here, we isolated a lineage of Env apex-directed neutralizing antibodies, N90-VRC38.01-11, using virus-like particles and conformationally stabilized Env trimers as B cell probes. A crystal structure of N90-VRC38.01 with a scaffolded V1V2 revealed a binding mode involving side-chain to side-chain interactions that reduced the distance the antibody loop must traverse the glycan shield, facilitating V1V2 binding via a non-protruding loop. The N90-VRC38 lineage identifies a solution for V1V2apex binding that provides a more conventional B cell pathway for vaccine design.